Factors that contribute to the failure of RFID usage in supply chain - Gan, Eng Hong (2010)
Radio frequency identification (RFID) is a technology with a great potential in many industries and a wide spectrum of possible uses. One of the first places where it is being used and where it promises excellent results is supply chain. Unfortunately RFID also brings with it some of its faults which can result in security threats. This paper is a result of a research conducted on the factors that contribute to the failure of RFID usage in supply chain. It firStly explains in detail the paths and methods this research used and elaborates more in depth about the research problem during which the research question and its scope are defmed. Threaten attributes is discussed in security problems of RFID in their supply chains. Following parts give introduction to the technology, its application and other issues addressed in the research to ensure better understanding of the subject. Current research and available literature are used do defme problems with security in RFID supply chains which is then joined with some practical experiences and experts opinions to create final fmdings, conclusions and recommendation. The scope of study for this project paper will focus on companies which implemented RFID in Malaysia by different industry sectors where the survey's questionnaire will be distributed to them. The total number of respondents involved in this survey will be 50 respondents. The data analysis was discussed includes of central tendency of mean, mode, and median, and measures of dispersion in terms of range and standard deviation, descriptive analysis and crosstabulation. Furthermore, it also uses analysis of correlation of t-test, ANOVA and Factorial ANOVA to check the relationship between the demographic profile and independent variable. Findings show that, three factors contribute to the failure of RFID usage in supply chain. Those three factors are unauthorized reading tag, change the data on the tag, physical damage and denial-of service attacks. Recommendations such as minimize tag time exposure, regularly check tags, use tag blocker, and authorization process.